Golden Lane Estate; Past, Present, and Future - Antoniou, Klitsa (My University, 2026)
Exhibit Golden Lane Gallery, London, UK Golden Lane Estate; Past, Present, and Future: A Design, Art and Community Legacy Competition Residency, Exhibit Studio. Sponsored by Exhibit Golden Lane Gallery and Leonardo European Exchange Program.